Genetic analysis of Pycr1 and Pycr2 in mice. Issue 1 (18th March 2021) - Stum, Morgane G; Tadenev, Abigail L D; Seburn, Kevin L; Miers, Kathy E; Poon, Pak P; McMaster, Christopher R; Robinson, Carolyn; Kane, Coleen; Silva, Kathleen A; Cliften, Paul F; Sundberg, John P; Reinholdt, Laura G; et al.
Abstract: The final step in proline biosynthesis is catalyzed by three pyrroline-5-carboxylate reductases, PYCR1, PYCR2, and PYCR3, which convert pyrroline-5-carboxylate (P5C) to proline. Mutations in human PYCR1 and ALDH18A1 (P5C Synthetase) cause Cutis Laxa (CL), whereas mutations in PYCR2 cause hypomyelinating leukodystrophy 10 (HLD10). Here, we investigated the genetics of Pycr1 and Pycr2 in mice. A null allele of Pycr1 did not show integument or CL-related phenotypes. We also studied a novel chemically-induced mutation in Pycr2 . Mice with recessive loss-of-function mutations in Pycr2 showed phenotypes consistent with neurological and neuromuscular disorders, including weight loss, kyphosis, and hind-limb clasping. The peripheral nervous system was largely unaffected, with only mild axonal atrophy in peripheral nerves. A severe loss of subcutaneous fat in Pycr 2 mutant mice is reminiscent of a CL-like phenotype, but primary features such as elastin abnormalities were not observed. Aged Pycr2 mutant mice had reduced white blood cell counts and altered lipid metabolism, suggesting a generalized metabolic disorder. PYCR1 and -2 have similar enzymatic and cellular activities, and consistent with previous studies, both were localized in the mitochondria in fibroblasts. Both PYCR1 and -2 were able to complement the loss of Pro3, the yeast enzyme that converts P5C to proline, confirming their activity as P5C reductases. In mice, Pycr1; Pycr2 double mutants were sub-viable and unhealthy compared to either single mutant, indicating the genes are largely functionally redundant. Proline levels were not reduced, and precursors were not increased in serum from Pycr2 mutant mice or in lysates from skin fibroblast cultures, but placing Pycr2 mutant mice on a proline-free diet worsened the phenotype. Thus, Pycr1 and -2 have redundant functions in proline biosynthesis, and their loss makes proline a semi-essential amino acid. These findings have implications for understanding the genetics of CL and HLD10, and for modeling these disorders in mice.